Effect of Victories and Defeats on the Attitude of Soccer Fans: a Study Concerning Pitchman, Involvement and Fanaticism - Fernando A. Fleury; Vitor Koki da Costa Nogami; José Afonso Mazzon; Andres Rodriguez Veloso (BBR: Brazilian Business Review)
This paper aims to analyze the attitude of soccer fans after the outcome of matches under the influence of a pitchman (celebrities and idols), involvement and fanaticism. The literature was supported by the concepts of happiness and attitude applied to sports, interacting with the literature on the influence of the pitchman (studies 1 and 2), involvement (study 3) and fanaticism (study 4). The data was collected in four rounds of the Brazilian soccer league, comprising 931 fans of the 16 best teams in the country. The data was analyzed using the GLM (General Linear Model). The findings indicate that the outcome of the match will have more influence on the attitude of fans than the endorsement of a pitchman, and that this influence is enhanced by the involvement and fanaticism of fans.